Tactical behaviors in men`s and women`s middle-distance global championship track finals - Comino, P.; Foster, C.; Renfree, A.; Casado, A. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To analyze tactical behaviors associated with performance in track middle-distance global championship finals.